Blood oxygen‐level dependent functional assessment of cerebrovascular reactivity: Feasibility for intraoperative 3 Tesla MRI - Fierstra, Jorn; Burkhardt, Jan‐Karl; van Niftrik, Christiaan Hendrik Bas; Piccirelli, Marco; Pangalu, Athina; Kocian, Roman; Neidert, Marian Christoph; Valavanis, Antonios; Regli, Luca; Bozinov, Oliver (Magnetic resonance in medicine, 2017)
Purpose To assess the feasibility of functional blood oxygen‐level dependent (BOLD) MRI to evaluate intraoperative cerebrovascular reactivity (CVR) at 3 Tesla field strength. Methods Ten consecutive neurosurgical subjects scheduled for a clinical intraoperative MRI examination were enrolled in this study. In addition to the clinical protocol a BOLD sequence was implemented with three cycles of 44 s apnea to calculate CVR values on a voxel‐by‐voxel basis throughout the brain. The CVR range was then color‐coded and superimposed on an anatomical volume to create high spatial resolution CVR maps. Results Ten subjects (mean age 34.8 ± 13.4; 2 females) uneventfully underwent the intraoperative BOLD protocol, with no complications occurring. Whole‐brain CVR for all subjects was (mean ± SD) 0.69 ± 0.42, whereas CVR was markedly higher for tumor subjects as compared to vascular subjects, 0.81 ± 0.44 versus 0.33 ± 0.10, respectively. Furthermore, color‐coded functional maps could be robustly interpreted for a whole‐brain assessment of CVR. Conclusion We demonstrate that intraoperative BOLD MRI is feasible in creating functional maps to assess cerebrovascular reactivity throughout the brain in subjects undergoing a neurosurgical procedure. Magn Reson Med 77:806–813, 2017. © 2016 International Society for Magnetic Resonance in Medicine